Hubungan Sikap Penderita dengan Tingkat Kepatuhan Pengobatan di Poli TB-MDR - Sari, Serly Novita; Yulanda, Nita Arisanti; Murtilita, Murtilita; Fahdi, Faisal Kholid; Mita, Mita (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT MDR-TB is a condition of patients who are resistant to drugs with the types of rifampin and isoniazid. According to the WHO Global Tuberculosis Report in 2020, new confirmed cases of MDR-TB are 58%, only 19% of MDR-TB patients are taking treatment due to non-adherence to treatment. The attitude of the patient which is feeling bored with MDR-TB treatment, and also small motivation and support from the family causing non-adherence in treatment. To analyze the relationship between patient attitudes and family support with the level of treatment adherence in the MDR-TB Polyclinic RSUD Dr. Soedarso. This research is a quantitative analytic with a cross sectional approach. Accidental sampling was used. Questionnaires were used to collect the data for the attitude, family support and medication adherence. The medical records were used for the observation of medication adherence. The statistical test in this study used the Spearman Rho test. Statistical tests showed that there was a relationship between family support and medication adherence, as seen from the p-value = 0.015 <0.05, unidirectional correlation, while there was no relationship between the attitude of the patient and the medication adherence because the p-value = 0.827 > 0.05, the correlation was not unidirectional. Good family support can make the level of treatment adherence of MDR-TB patients high, while the attitude of patients who are very good does not necessarily mean that the level of adherence to treatment is high. Keywords: MDR-TB, Medication Compliance, Family Support, Attitude  ABSTRAK TB-MDR merupakan kondisi penderita resistan terhadap obat dengan jenis rifampisin dan isoniazid. Menurut WHO Global Tuberculosis Report pada tahun 2020 kasus baru terkonfirmasi TB-MDR yaitu 58%, hanya 19% penderita TB-MDR yang melakukan pengobatan dikarenakan tidak patuh pengobatan.  Sikap penderita yaitu merasa jenuh dengan pengobatan TB-MDR dan dukungan keluarga kurang memotivasi serta mendukung dengan baik menyebabkan ketidakpatuhan dalam pengobatan. Menganalisis hubungan antara sikap penderita dan dukungan keluarga dengan tingkat kepatuhan pengobatan di Poli TB-MDR RSUD dr. SoedarsoPenelitian ini merupakan kuantitatif analitik dengan pendekatan cross sectional. Pengambilan sampel menggunakan Accidental sampling. Pengumpulan data dari kuesioner sikap, dukungan keluarga dan kepatuhan pengobatan, serta menggunakan rekam medis untuk observasi kepatuhan pengobatan. Adapun uji statistik dalam penelitian ini menggunakan uji Spearman Rho. Uji statistik didapatkan adanya hubungan dukungan keluarga dengan kepatuhan pengobatan dilihat dari nilai p-value = 0,015 < 0,05 sedangkan tidak ada hubungan antara sikap penderita dengan kepatuhan pengobatan karena nilai p-value = 0,827 > 0,05. Dukungan keluarga yang baik dapat membuat tingkat kepatuhan pengobatan penderita TB-MDR tinggi sedangkan sikap penderita yang sangat baik belum tentu tingkat kepatuhan pengobatannya tinggi. Kata Kunci : TB-MDR, Kepatuhan Pengobatan, Sikap Penderita